Professional development and professionalization of adult education in Cyprus: views and perceptions of adult educators - Ioannou, Nicoletta (2018)
Adult educators have been identified in the academic and policy literature as crucial to the success of national and regional strategies to deliver quality teaching to adult learners who require new knowledge and skills to meet changing social and economic needs. However, the majority of adult educators are part time practitioners who frequently lack any formal training or specialized expertise for teaching adults (Andersson, Köpsén, Larson and Milana, 2012; Jarvis, 2004). Across the world, limited attention is given to their professional development, leaving the majority of them to assume this responsibility by themselves. This is the case in Cyprus. The Cypriot adult education sector is characterised by part-time practitioners with low pay, limited professional development opportunities and uncertain career prospects. The professionalization of the sector and the development of adult education as a recognised profession has not been a priority.